The creative mufti: Ibn Abidin (d.1252 AH/1836 CE) - Ali, Mohammed Farid (International Institute of Advanced Studies (IAIS) Malaysia and Pluto Press (London), 2012)
The eminent thirteenth century /early–nineteenth century Damascene scholar Muhammad Amin ibn Umar ibn Abd al-Aziz, better known as Ibn Abidin al-Shami especially in South Asian Hanafite circles, was an Alid sayyid descended from Ismail ibn Jafar al-sadiq. Born in 1198 AH /1784 CE in al-Qunawat quarter of the city of Damascus he took his early education in the Shafi legal school, then adopted the Hanafa juridical school. Under the leading Hanafi Shaykhs Shakir al-Uqqad al-Umari and Said al-Halabi he studied inheritance law & mathematics, legal theory, the Hadith disciplines, Qur’an exegesis, mysticism (tasawwuf), as well as various rational disciplines (ulum aqliyah)...........